Model of Polycrystalline Inelastic Deformation with Grain Boundary Sliding Description - Trusov P. V.; Shveykin A. I.; Sharifullina E. R.; Kondratev N. S. (Advanced Materials and Nanotechnology, 2014)
Title screen